Anaphylactoid reactions induced by a fluorocarbon blood substitute - Zhang Sheng-nian; Liu Chun-fang; Dong Jin-wu; Ding Xun-cheng (Acta Pharmacologica Sinica; Vol 6, No 3 (September 1985): Acta Pharmacologica Sinica, 2016)
The potential mechanisms of fluorocarbon emulsion(FCE)-induced anaphylactoid reactions were stufied by detecting the immunological responses and the blood vessel active content. The passive cutaneous anaphylaxis(PCA) test in rats determined by FCE antigen was negative. The precipitating fluorocarbon emulsion reaction antibody(FRA) in sera of rabbit 20 min and 24 h after iv infusion of FCE (10 mL/kg) by reversible single radioactive immunodiffusion(RSRI)was positive. Histamine and 5-HT content in rabbit were decreased by 79% and 92% respectively, 10 min after infusion of FCE platelet counts fell to 67%, WBC to 47% and P/L value depressed as much half of that before infusions. Small arteriole of lungs were filled with macrophages. These results indicated that the mechanisms of FCE-induced anaphylactoid reactions did not involve histamine and 5-HT release,but associated with FCE-FRA complex and macrophage-stasis in pulmonary vessels.